PENGGUNAAN METODE AL-MIFTAH LIL ULUM DALAM MEMBACA KITAB KUNING - Muniro Muniro; Imam Bukhori; Muhammad Hifdil Islam (LP2M Universitas Ibrahimy, 2023)
The Yellow Book is an identity and is the main focus in Islamic boarding school education, but the material is not easy to learn. Therefore, PP Lubbul Labib Banat I Kedungsari adopted a new method from PP Sidogiri Pasuruan, namely Al-Miftah Lil Ulum since 2017. This research aims to determine the process of using the Al-Miftah method starting from planning, implementing and evaluating it. This research uses a case study qualitative research type with data collection techniques; observation, interview, and documentation. The subjects studied were 31 students and 7 teachers. Meanwhile, to check the validity of the data using source triangulation. The results of the research show that at each stage there are several discussions, namely; At the planning stage include; learning objectives and experiences, determining learning activities, the people involved, materials, facilities and evaluation planning. The implementation stage concerns activities during the learning process; opening, apperception, giving new material, training, ending learning evaluation. At the evaluation stage it is divided into 2 namely for students and teachers. During the use of this method, the learning process has been running quite well and effectively. The indicators in this study are grammar and writing.